Government (Industrial) Policies for Competitiveness in a Global Economy - Tarr, David (International Finance Corporation, Washington, DC, 2017)
The general principle is that it is crucial for the government to provide a stable macroeconomic environment conducive to business development with a clear, transparent and neutral regulatory environment and neutral incentives to all firms and industries. Clear, transparent and neutral incentives (those which do not distinguish by sector or firm) are crucial so that entrepreneurial innovation is rewarded more highly than rent-seeking activities. The economy must provide its most talented members with the incentive to engage in entrepreneurial activities such as starting or expanding firms, developing new products and lowering costs. If the economy provides extensive subsidies or tax exemptions to industries or firms, or presents a difficult regulatory framework within which to do business, corruption will be encouraged and, crucially, talented people will find it more profitable to engage in the socially wasteful activity of lobbying the government for subsidies, protection, tax or regulatory relief. This socially wasteful lobbying is especially harmful because it attracts scarce entrepreneurial talent that would otherwise be devoted to helping the economy grow. First, there is the risk that the wrong industries will be identified. The market is a more reliable indicator of the industries that have comparative advantage than any economic model or theory. Over time this is particularly true, as comparative advantage changes with technological development. Moreover, targeting industries as "winners" will generate rent-seeking where industries will spend resources to obtain government subsidies rather than attempting to compete more effectively on the market. Governments often find it difficult to resist these pressures. And assistance that is designed to be temporary may become permanent. Thus, experience in most countries has shown that a government policy of attempting to "pick winners" is highly counter productive.